2013
DOI: 10.1051/0004-6361/201322562
|View full text |Cite
|
Sign up to set email alerts
|

The au-scale structure in diffuse molecular gas towardsζ Persei

Abstract: Context. Spatial structure in molecular material has a strong impact on its physical and chemical evolution and is still poorly known, especially on very small scales. Aims. To better characterize the small-scale structure in diffuse molecular gas and in particular to investigate the CH + production mechanism, we study the spatial distribution of CH + , CH, and CN towards the bright star ζ Per on scales in the range 1−20 AU. Methods. We use ζ Per's proper motion and the implied drift of the line of sight throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…On the one hand, within time-scales of tens of years, the ISM absorption can be considered to be stable (e.g. Boissé et al 2013), hence it does not introduce spurious variability that may interfere with planet detections. On the other hand, ISM absorption dims the stellar activity signal, up to the point where it may mask the Ca ii line core variability, leading to a mis-or non-detection of periodicities connected to stellar rotation and activity cycles, though they may be clearly present in the periodograms obtained from analysing the radial velocity measurements.…”
Section: Relevance For Exoplanet Studiesmentioning
confidence: 99%
“…On the one hand, within time-scales of tens of years, the ISM absorption can be considered to be stable (e.g. Boissé et al 2013), hence it does not introduce spurious variability that may interfere with planet detections. On the other hand, ISM absorption dims the stellar activity signal, up to the point where it may mask the Ca ii line core variability, leading to a mis-or non-detection of periodicities connected to stellar rotation and activity cycles, though they may be clearly present in the periodograms obtained from analysing the radial velocity measurements.…”
Section: Relevance For Exoplanet Studiesmentioning
confidence: 99%
“…Such a technique applies from the solar neighbourhood towards nearby stars (e.g. Savage et al 1977;Boissé et al 2013) to the gas in and around high-redshift galaxies revealed by damped Lyman-α systems (DLAs; e.g. Levshakov et al 1989;Ge et al 1997;Petitjean et al 2000;Cui et al 2005;Srianand et al 2005;Noterdaeme et al 2008;Jorgenson et al 2010;Carswell et al 2011;Balashev et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These observations imply a population of dense au-scale clouds in the ISM or changes in ionization or depletion over time, but are restricted to trace neutral species. Boissé et al (2013) studied the spatial distribution of CH + , CH and CN on scales ranging 1-20 au for a single sightline towards Zeta Per, finding the neutral species to be uniformly distributed and a CH + excess implying its production in very small localized active regions of only a few au. Data for UV absorption-lines can probe dominant ions and provide further information on the physical conditions; time-variable UV lines have been found by e.g.…”
Section: Introductionmentioning
confidence: 99%